Resolver as seguintes equações do primeiro grau:
A)-2m(-m+2)=3(2m+1)

B)12m+3(m-1)=-2(m+1)+12

C)2(x-1)=0

D)-3(m+2)=1 E)2(x+2)=12

E)m=-3(m-4)

G)2(m+5)=-3(m-5)

H)-2(y+4)=-7+9(y-1)

I)5(x-4)+4=2(-2x-2)+9

J)-5(x-4)+4=2(-2x-2)+9

K)-2(m-5)+3m=-(m+2)-7

L)-(x+5)-6+-9(x-3)-2

M)x-7+2(x-4)=-3(x+2)-8

1

Respostas

2014-07-12T22:16:20-03:00

 E)m=-3(m-4)  -> m=-3m+12  m+3m=12  4m=12 m=12/4 m=3
B)12m+3(m-1)=-2(m+1)+12  -> 12m+3m-3=-2m-2+12  17m=13  m=13/17
 
C)2(x-1)=0 -> 2x-2=0  2x=2  x=2/2 =1 
1 5 1